2016
DOI: 10.1080/10790268.2016.1139771
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein as an available biomarker determining mental component of health-related quality of life among individuals with spinal cord injury

Abstract: Although CRP and leptin levels were not related with total scores of SF-36 questionnaire, CRP can be more useful in determining mental component of HRQL whereas leptin can be a determinant of physical component. The combined consideration of these two biomarkers may help to predict HRQL in individuals with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition, compared with participants without fatigue, participants with fatigue and low-grade inflammation as measured by CRP were shown to have mental health problems, including psychological distress, depression, and sleep problems [ 72 ]. Previously, etiological studies showed a negative association between serum CRP levels and the SF-36 MH score in patients with a neural injury, such as spinal cord injury [ 21 ]. Depressed participants were reported to have significantly higher serum C3 levels than healthy participants [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compared with participants without fatigue, participants with fatigue and low-grade inflammation as measured by CRP were shown to have mental health problems, including psychological distress, depression, and sleep problems [ 72 ]. Previously, etiological studies showed a negative association between serum CRP levels and the SF-36 MH score in patients with a neural injury, such as spinal cord injury [ 21 ]. Depressed participants were reported to have significantly higher serum C3 levels than healthy participants [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…High systemic levels of these inflammatory markers are well known to be associated with increased risk for chronic inflammatory diseases [ 2 , 19 , 20 ]. In addition, elevation of circulating levels of CRP and C3 may be associated with impaired quality of life (QOL) and mood disturbance [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in lipid profiles have been observed by level of injury and sex for people with SCI. Sabour et al [ 99 ], Jörgensen et al [ 75 ], and Farkas et al [ 5 ] found that men with SCI had significantly lower HDL-C levels than women with SCI [ 75 ]. In addition, Farkas et al [ 5 ] observed that men with SCI had a higher TC:HDL-C ratio than women with SCI.…”
Section: Dyslipidemia After Scimentioning
confidence: 99%
“…Recent studies suggest the role of inflammatory and endocrine clinical blood markers, including inflammatory cytokines, C-reactive protein, and dehydroepiandrosterone (DHEA) in the development and chronicity of symptoms, particularly with mobility limitation, depression, sleep deprivation, fatigue, and HRQoL [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. To the best of our knowledge, there is limited evidence on the associations of these clinical blood markers with symptom burden and HRQoL.…”
Section: Introductionmentioning
confidence: 99%